I was working on radical equations and I came across a few problems where I got answers that worked when I checked, but were not listed as solutions. My teacher's only explanation was, "just because." Here is one problem where the only solution is $1$.


How I solved it




$x= \{-2, 1\}$

Then plugging both numbers back in, I get

$1 = \sqrt{2-1}$

$1 = \sqrt{1}$

$1 = 1$


$-2 = \sqrt{2--2}$

$-2 = \sqrt{4}$

The square root of $4$ can be both $-2$ because $-2 \times -2 = 4$ and $2$. $1$ is the only solution listed and my teacher says that it's right.

What is the explanation for this? Why isn't $-2$ a solution for the problem?

  • 9
    $\begingroup$ "Just because" is a terrible response to anything math-related. $\endgroup$ – anomaly Apr 17 '15 at 15:20

This is due to notation. When we write $\sqrt{n}$ we mean only the positive square root of $n$. If we wished to include both negative and positive solutions, we would write $\pm\sqrt{n}$.

I know this can be irritating, but it is the convention that is used, since square root would not be a function if it gave multiple values.


The issue arises from the second line.

The statement: $ x = \sqrt{2-x} $

Is not equivalent to the statement: $ x^2 = 2 - x $

Think of it like this, although the first statement implies the second, the second does not imply the first (since you'd need to introduce the negative square root).

$ x=-2 $ Isn't actually a solution to your original equation, since you're only taking the positive square root. You just have to remember that when squaring, you can always introduce incorrect 'solutions' simply because A = B is not logically equivalent to A^2 = B^2.


When we use a radical, $\sqrt[n]{~~}$, we mean to take the principal $n^{th}$ root, which in the case of positive real numbers will always be a positive real number.

In other words $\sqrt{4} = 2$ and only $2$. $\sqrt{4}\neq -2$ even though $(-2)^2 = 4$

If we were to allow for multiple roots, we can use $(~~)^{\frac{1}{n}}$ to refer any element of the set of all $n^{th}$ roots, noting that this is a multivalued function (and thus not a function at all, since to be a function we require it have a single output for any given input).

Here we have $4^{\frac{1}{2}} \in \{2,-2\}$

In your specific example, $x = \sqrt{2-x}$, we have that $x$ being equal to the principle square root of something presumably positive, must itself also be positive, and so $x=1$ is the only solution (as shown by your algebra above).


The answer, as already the others has highlighted, is that $\sqrt{4} \neq -2$, but to aid you in the actual expression evaluation, consider that $\sqrt{x^2} \neq x$, but $\sqrt{x^2} = \left| x \right|$.


Omar already gave a good answer, but I wanted to expand on this part:

You just have to remember that when squaring, you can always introduce incorrect 'solutions' simply because A = B is not logically equivalent to A^2 = B^2.

If you have an equation, and you multiply both sides by another equation, you don't always get the same equation.

For example, $(x-2)=0$. If you multiply both sides by $(x+5)$, you'll get $(x-2)(x+5)=0$. The second equation has solutions $x=2,-5$, and the first has $x=2$ only.

In Omar's example, since $A=B$, he is multiplying both sides by $A$. In general, you can only multiply both sides by a non-zero constant to always preserve logical consistency. In your example, you're multiplying both sides by $(2-x)^{1/2}$. Since $(2-x)^{1/2}$ is not a non-zero constant, it does not always preserve logical consistency.

For example, you can multiply both sides by $4$, and it doesn't change the solutions to the equation. However, it will sometimes preserve the equation in something like the following example: $(x-4)^4=0$, if you multiply both sides by $(x-4)^2$, the result, $(x-4)^6=0$, will have the same set of solutions.

  • 1
    $\begingroup$ To go from $A=B$ to $A^2=B^2$ is just a property of equality, but getting from $A^2=B^2$ to $A=\pm B$ is not simply a matter of multiplying or dividing by $A$. The actual proof looks more like $$A^2-B^2=(A-B)(A+B)=0\implies A-B=0\lor A+B=0.$$ $\endgroup$ – Mario Carneiro Apr 17 '15 at 9:46
  • $\begingroup$ I don't know exactly what you mean by the action, "to go from". W.r.t. the two statements, $A=B$ and $A^2 = B^2$, they do not necessarily have the same solution set. $\endgroup$ – user38858 Apr 17 '15 at 19:21
  • $\begingroup$ "To go from" here means that if $A=B$ is true, then $A^2=B^2$ is true, i.e. a forward implication. Note that this is actually the opposite order from that with which we solve equations; usually you start with the complicated equality and perform simplifications on it until you have a tautology. For example if you are asked to solve $A^2=B^2$ you can simplify it to $A=B$ and have a solution, since $A=B\implies A^2=B^2$. (You may not have found all solutions, but you have not introduced extraneous ones this way.) If you want to find all solutions, then all steps must be biconditional. $\endgroup$ – Mario Carneiro Apr 17 '15 at 19:53

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.